Turn-Taking Strategies of Conversation in Warren Edward Buffet Interview on Squawk Box Business News - Yasa Ayatina Ashidiq; Ice Sariyati (STKIP PGRI Tulungagung, 2022)
Conversation is a human daily activity that involves the speaker shift. The basic pattern of talk to get shifting is “A-B-A-B-A-B”. Turn-taking strategies is necessary elements in conversation. Therefore, the researcher is interested in analyzing turn-taking strategies. The research problems are: 1) What types of turn-taking strategies are used by the participants in interview with Warren Edward Buffett on Squawk Box Business News, 2) How are the allocation of turn-taking strategies in interview with Warren Edward Buffett on Squawk Box Business News? This research used qualitative descriptive method. This research used the theory from Stenstrom, (1994) and Sacks et al., (1974) to answer research problems. The research findings showed that 62 data of turn-taking strategies types in this research were taking the floor (45 data) divided into starting up (15 data), taking over (9 data), and interrupting (13 data). In addition, there were holding the floor (13 data) and Yielding the floor (17 data) divided into prompting (7data), appealing (5 data), and giving up (5 data). Moreover, the findings data for the turn-allocation of turn-taking strategies were the technique of current speaker selects next speaker (28 data) and for next speaker self-select technique (34 data). Turn-taking types help conversation flow smoothly. Especially taking the floor strategies. It means every participants in conversation has a cooperative role. Beside, many participants did not wait for Turn Relevance Place (TRP) to have turns. Instead, they preferred to take turn by using the self- selection allocation. Much better, for participants in interview just wait for interviewee gave the turn.